posted by Brett on .
Given the Data:
N2(g) + O2g) = 2NO(g) delta H = 180.7kj, 2NO(g) + O2(g) = 2NO2(g) delta H = 0113.1kj, 2N2O(g) = 1N2(g) + O2(g) delta H = -163.2kj.
Using Hess’s Law calculate delta H for the reaction:
N2O(g) + NO2(g) = 3NO(g)
multiply equation 1 by 2 and dH x 2.
Reverse equation 2 and change sign dH.
Balance equation 3(it isn't balanced now).
Add the three equations and add dHs. This will get
2NO2 + 2N2O ==> 6NO which is twice what you want. So divide the final equation by 2 and divide sum dH by 2.